2005
DOI: 10.5194/acp-5-2869-2005
|View full text |Cite
|
Sign up to set email alerts
|

Organic, elemental and inorganic carbon in particulate matter of six urban environments in Europe

Abstract: Abstract.A series of 7-week sampling campaigns were conducted in urban background sites of six European cities as follows: Duisburg (autumn), Prague (winter), Amsterdam (winter), Helsinki (spring), Barcelona (spring) and Athens (summer). The campaigns were scheduled to include seasons of local public health concern due to high particulate concentrations or findings in previously conducted epidemiological studies. Aerosol samples were collected in parallel with two identical virtual impactors that divide air pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
82
3
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(98 citation statements)
references
References 33 publications
8
82
3
5
Order By: Relevance
“…A relatively big percentage of it is probably found as CaCO 3 due to the calcitic nature of the crustal rock in Greece which is supported by the results of a recent study (Sillanpää et al, 2005). Similar with Ca 2+ unimodal distribution is observed for NO − 3 , Cl − and Na + , as they are mainly found in the CPM.…”
Section: Identification Of Major Elements and Ions Distribution In Tsupporting
confidence: 76%
See 2 more Smart Citations
“…A relatively big percentage of it is probably found as CaCO 3 due to the calcitic nature of the crustal rock in Greece which is supported by the results of a recent study (Sillanpää et al, 2005). Similar with Ca 2+ unimodal distribution is observed for NO − 3 , Cl − and Na + , as they are mainly found in the CPM.…”
Section: Identification Of Major Elements and Ions Distribution In Tsupporting
confidence: 76%
“…The analyzed FPM mass ranges from 39% to 45% of the total FPM mass, with the exception of Athinas St. in the morning where this percentage appears lower at approximately 29%. Ions such as CO − 3 which has been recently identified in great amounts in the Athens atmosphere (Sillanpää et al, 2005), OH − , lighter elements that PIXE can not successfully analyze, strongly bound water that remains at the low RH of the weighing chamber (Harrison et al, 2003) other mineral compounds (including bound oxygen and nitrogen), as well as carbon, organics and polymers, are believed to constitute the biggest percentage of the unknown part of the PM. According to recent studies (D'Alessandro et al, 2003), these compounds usually constitute more than 50% of the urban aerosol mass.…”
Section: Identification Of Major Elements and Ions Distribution In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Zappoli et al (1999); Ricard et al (2002) and Yttri et al (2007a) all presented concentrations observed at rural background sites, while the studies by Viidanoja et al (2002), Sillanpää et al (2005), Glasius et al (2006) and Saarikoski et al (2007) reported observation from the urban environment. Of these studies, only three accounted for the positive sampling artefacts of OC.…”
Section: Introductionmentioning
confidence: 91%
“…The carbonatic carbon component was not considered in this work as previous studies reported that carbonate is negligible in PM 10 at most European areas. Exceptions are coastal sites in south Europe (ten Brink et al, 2004;Sillanpää et al, 2005;Perrone et al, 2011) or peculiar situations (Querol et al, 2009;Cuccia et al, 2011).…”
Section: Thermal-optical Transmittance Analysismentioning
confidence: 99%